An assistive robotic device that can synchronize to the pelvic motion during human gait training - Aoyagi, D.; Ichinose, W.E.; Harkema, S.J.; Reinkensmeyer, D.J.; Bobrow, J.E. (9th International Conference on Rehabilitation Robotics, 2005. ICORR 2005, 2005)
We are developing a robotic device, PAM (pelvic assist manipulator), that assists the pelvic motion during human gait training on a treadmill. PAM allows naturalistic motion of pelvis actuated by six pneumatic cylinders, which, combined with a nonlinear force-tracking controller, provide backdrivability and large force output at a relatively low cost. PAM can act as a teach-and-replay device with a PD position controller driving the pelvis onto the reference trajectory specified with or without the help of therapists. During initial experiments with unimpaired subjects, we encountered a problem in which the subjects had difficulty synchronizing their movements with the gait pattern reproduced by PAM, even though that gait pattern had been sampled from the subjects themselves. We introduced footswitches to detect the gait timing and developed a feedback control algorithm that adjusts the play-back speed of the gait pattern in real-time. The feedback algorithm is presented, along with data that shows the effectiveness of the algorithm in synchronizing the robotic assistance during stepping by unimpaired subjects, even when the subjects change their step size and period.